Capability to self-mobilization of individually - psychological possibilities as constituting personal mobility of pupils of a comprehensive school - Artyushenko A.A. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2010)
Features of self-mobilization of natural possibilities of pupils are construed during executing physical exercises and commitments of different character. The concept «personal mobility» is given. 128 pupils of elementary grades, 126 adolescents and 106 pupils of the higher classes participated in experiment. It is exhibited that at pupils the range of individual parameters of self-mobilization constitutes from 20 up to 40 %. The greatest gain of parameters of self-mobilization is fixed at adolescents - 47,4 %, at pupils of the higher school age - 42,1 %, at pupils of elementary grades - 29,7 %.